Suppression of Natural Killer Cell Activity by Regulatory NKT10 Cells Aggravates Alcoholic Hepatosteatosis - Cui, Kele; Yan, Guoxiu; Zheng, Xiaodong; Bai, Li; Wei, Haiming; Sun, Rui; Tian, Zhigang (Frontiers in Immunology, 2017)
We and others have found that the functions of hepatic NK cells are inhibited but invariant NKT (iNKT) cells become activated after alcohol drinking, leaving a possibility that there exists interplay between NK cells and iNKT cells during alcoholic liver disease (ALD). Here, in a chronic plus single-binge ethanol consumption mouse model, we observed that NK cells and interferon-γ (IFN-γ) protected against ethanol-induced liver steatosis, as both wild-type (WT) mice treated with anti-ASGM1 antibody and IFN-γ-deficient GKO mice developed more severe alcoholic fatty livers. As expected, IFN-γ could directly downregulate lipogenesis in primary hepatocytes in vitro. On the contrary, iNKT cell-deficient Jα18-/- or IL10-/- mice showed fewer alcoholic steatosis, along with the recovered number and IFN-γ release of hepatic NK cells, and exogenous IL-10 injection was sufficient to compensate for iNKT cell deficiency. Furthermore, NK cell depletion in Jα18-/- or IL10-/- mice caused more severe hepatosteatosis, implying NK cells are the direct effector cells to inhibit liver steatosis. Importantly, adoptive transfer of iNKT cells purified from normal but not IL-10-/- mice resulted in suppression of the number and functions of NK cells and aggravated alcoholic liver injury in Jα18-/- mice, indicating that IL-10-producing iNKT (NKT10) cells are the regulators on NK cells. Conclusion: Ethanol exposure-triggered NKT10 cells antagonizes the protective roles of NK cells in alcoholic hepatosteatosis.